Performance of Four Superior Tomato Lines on Combination of Cow Manure and NPK Fertilizer - Sri Rustianti; Sri Mulatsih; Widya Oktafia Hutagalung (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
Variety improvement approach aims to address tomato production problems. Objective: to identify performance of four tomato superior lines on combination of cow manure and NPK fertilizer. It used split plot design with main plot of four tomato superior lines and subplot of five combination dosages of cow manure and NPK fertilizer. Results: performance of four tomato superior lines did not significantly influence plant height, number of branches, flowering age and harvesting age, but significantly influenced the number and weight of fruit; Combination of cow manure and NPK fertilizer insignificantly influenced performance of four tomato superior lines; Interaction of superior lines with combination of cow manure and NPK fertilizer insignificantly influenced performance of four superior lines. Performance of each superior line was different to each fertilizer combination. The heaviest fruit weight per plant of GH 6 used dosage of 600 kg/ha NPK, GH 12 used combination of 20 ton/ha cow manure and 300 kg/ha NPK, GH 13 used combination of 20 ton/ha cow manure and 300 kg/ha NPK. This can become basis for determining future potential tomato development.